2018
DOI: 10.1016/j.jpsychores.2018.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Retrospectively reported childhood adversity is associated with asthma and chronic bronchitis, independent of mental health

Abstract: Several researchers have raised the concern that the cross-sectional association of retrospectively reported childhood adversity with self-reported onset of asthma and chronic bronchitisin adulthood may be confounded, as well as mediated by an individual's mental health. The aim of this study was to assess the effect of retrospectively reported childhood adversity on self-reported onset of asthma and chronic bronchitis in adulthood, independent of potential confounding and mediating variables (including respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 108 publications
(154 reference statements)
1
19
0
Order By: Relevance
“…respondent's mental health may mediate the influence of CPA on physical health outcomes (Sheikh, 2018d). We have presented an estimation approach, as well as its underlying assumptions for independent effects, using an empirical example.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…respondent's mental health may mediate the influence of CPA on physical health outcomes (Sheikh, 2018d). We have presented an estimation approach, as well as its underlying assumptions for independent effects, using an empirical example.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is particularly important to note that if the magnitude of association between CPA and COPD and migraine is small, then the results (and consequently the inferences) should be interpreted cautiously. We recommend that future studies assessing the association between retrospectively reported CPA and physical health outcomes adjust for indicators of current mood/psychological state to control for mood-congruent recall bias (Sheikh, 2018d).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations